2017
DOI: 10.1002/bmc.4005
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a sensitive UHPLC–MS/MS method for quantitative analysis of farrerol in rat plasma: Application to pharmacokinetic and bioavailability studies

Abstract: Farrerol is a 2,3-dihydro-flavonoid isolated from rhododendron. In this study, a sensitive and selective ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method was developed for the determination of farrerol in rat plasma. Liquid-liquid extraction by ethyl ether was used for sample preparation. Chromatographic separation was achieved on an Agilent UHPLC XDB-C column (2.1 × 100 mm, 1.8 μm) with water and methanol (30:70, v/v) as the mobile phase. An electrospray source was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…UHPLC-MS/MS model for the estimation of farrerol in rat plasma using 50 μl of plasma over the 2-88-1440 ng/ml range has been developed and validated (Piao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…UHPLC-MS/MS model for the estimation of farrerol in rat plasma using 50 μl of plasma over the 2-88-1440 ng/ml range has been developed and validated (Piao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, glucuronide metabolites were also detected in urine by UHPLC-MS in the present work. With respect to pharmacokinetic and bioavailability studies of farrerol, a sensitive LC-MS method developed and validated for the quantitation of farrerol in rat plasma revealed that farrerol is rapidly absorbed and slowly eliminated in rats when administered orally, but is quickly eliminated when administered intravenously [34]. These results provide a theoretical foundation for the study of farrerol metabolites in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The 18 rats were divided into six groups (groups 1, 3, 5: blood experimental group, bile experimental group, urine and feces experimental group; groups 2, 4, 6: blood blank group, bile blank group and urine and feces blank group) and fasted for 12 h before operation. Farrerol powder was suspended in 0.5 wt% aqueous carboxymethyl cellulose sodium (CMC-Na) and intragastrically administered to experimental groups at a dose of 20 mg/kg [34], while an equivalent dose of CMC-Na solution was given to blank groups. All experiments complied with the Guide for the Care and Use of Laboratory Animals of the U.S. National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation